Screening for the at‐risk mental state in educational settings: A systematic review. Issue 6 (27th December 2019) - Howie, Clare; Potter, Claire; Shannon, Ciaran; Davidson, Gavin; Mulholland, Ciaran
Abstract: Aim: The at‐risk mental state (ARMS) allows clinicians to identify individuals who have an increased risk of developing psychosis. At present, most screening for psychosis‐risk is carried out within help‐seeking populations; however, screening within educational settings may allow clinicians to identify individuals at‐risk earlier and to increase the rate of detection. This review aimed to examine screening for the ARMS in educational settings, with the key questions: what screening tools have been used in educational settings, can screening in educational settings detect individuals with ARMS, what threshold scores in screening tools indicate a positive screen in educational settings, are there comorbid mental health conditions associated with the ARMS in educational settings? Methods: Searches were carried out in PsycINFO, MEDLINE, EMBASE, Scopus and Web of Science and reference lists of included articles searched. Results were summarized using narrative synthesis. Results: Nine papers were included for narrative synthesis. A variety of screening tools have been used when screening for the ARMS in educational settings. The majority of studies have been conducted in schools. The prevalence of the ARMS reported in ranges from 1% to 8%. Conclusions: The ARMS indicates the presence of distressing symptoms for which intervention may be beneficial. Screening programmes within educational settings may allow outreach for prodromal symptoms at an earlier stage than clinical settings currently provided for.